Active layer and permafrost thermal regimes in the ice-free areas of Antarctica - Hrbáček, Filip (2023)
Ice-free areas occupy <0.5% of Antarctica and are unevenly distributed across the continent. Terrestrial ecosystem dynamics in ice free areas are strongly influenced by permafrost and the associated active layer. These features are the least studied component of the cryosphere in Antarctica, with sparse data from permanent study sites mainly providing information related to the ground thermal regime and active layer thickness (ALT). One of the most important results of the International Polar Year (IPY, 2007/08) was an increase in ground thermal regime monitoring sites, and consequently our knowledge of Antarctic permafrost dynamics. Now, 15 years after the IPY, we provide the first comprehensive summary of the state of permafrost across Antarctica, including the sub-Antarctic Islands, with analyses of spatial and temporal patterns of the dominant external factors (climate, lithology, biota, and hydric regime) on the ground thermal regime and active layer thickness. The mean annual ground temperatures of the active layer and uppermost part of the permafrost in Antarctica remain just below 0 °C in the warmest parts of the Antarctic Peninsula, and were below −20 °C in mountainous regions of the continent. The ALT varies between a few cm in the coldest, mountainous, parts of the Transantarctic Mountains up to >5 m in bedrock sites in the Antarctic Peninsula. The deepest and most variable ALTs (ca. 40 to >500 cm) were found in the Antarctic Peninsula, whereas the maximum ALT generally did not exceed 90 cm in Victoria Land and East Antarctica. Notably, found that the mean annual near-surface temperature follows the latitudinal gradient of −0.9 °C/deg. (R2 = 0.9) and the active layer thickness 3.7 cm/deg. (R2 = 0.64). The continuous permafrost occurs in the vast majority of the ice-free areas in Antarctica. The modelling of temperature on the top of the permafrost indicates also the permafrost presence in South Orkneys and South Georgia. The only areas where deep boreholes and geophysical surveys indicates discontinuous or sporadic permafrost are South Shetlands and Western Antarctic Peninsula.